Perilaku Peangambilan Keputusan tentang Kesehatan Ibu dan Anak dalam Tradisi Perkawinan Nyentana: Studi Kasus di Desa Gadungan Tabanan Bali - Kadek Sri Ariyanti; Triyana Puspa Dewi; Ni Luh Astri Indraswari; Putu Arik Herliawati; Made Dewi Sariyani (Direktorat Politeknik Kesehatan Makassar, 2025)
The nyentana marriage tradition has implications for various aspects of family life, including decision-making regarding family health. Traditional customs and norms can influence how individuals make decisions related to health. This study aims to explore the factors that influence decision-making behavior regarding maternal and child health within the nyentana marriage tradition in Gadungan Village, Tabanan, Bali. This study uses a qualitative design with a case study approach. The participants in this study are families who have been practicing the Nyentana marriage tradition for at least one year, totaling 10 individuals, selected through purposive sampling. Data collection was conducted through interviews using a semi-structured guide, spanning a duration of one month. Data analysis was conducted thematically, with data validation through triangulation and member checking. Key informants in this study were village midwives and community leaders. The factors influencing decision-making regarding maternal and child health within the nyentana marriage tradition in Gadungan Village, Tabanan, Bali, are: 1) Cultural norms and traditions; 2) Knowledge and access to health information; 3) Family economy; Family support; and 5) Environment Decision-making regarding maternal and child health in the nyentana marriage tradition is greatly influenced by the active role of women. Factors related to decision-making regarding maternal and child health include cultural norms and traditions, knowledge and access to health information, family economy, family support, and social environment. The results of this study are expected to contribute to the development of maternal and child health programs that are responsive to local traditions and cultures. Keywords: Decision-making; health; Nyentana tradition